Review: Head and Eye Movements and Gaze Tracking in Baseball Batting. Issue 7 (July 2021) - Toole, Andrew J.; Fogt, Nick
Abstract : SIGNIFICANCE: After a 30-year gap, several studies on head and eye movements and gaze tracking in baseball batting have been performed in the last decade. These baseball studies may lead to training protocols for batting. Here we review these studies and compare the tracking behaviors with those in other sports. Baseball batters are often instructed to "keep your eye on the ball." Until recently, the evidence regarding whether batters follow this instruction and if there are benefits to following this instruction was limited. Baseball batting studies demonstrate that batters tend to move the head more than the eyes in the direction of the ball at least until a saccade occurs. Foveal gaze tracking is often maintained on the ball through the early portion of the pitch, so it can be said that baseball batters do keep the eyes on the ball. While batters place gaze at or near the point of bat-ball contact, the way this is accomplished varies. In some studies, foveal gaze tracking continues late in the pitch trajectory, whereas in other studies, anticipatory saccades occur. The relative advantages of these discrepant gaze strategies on perceptual processing and motor planning speed and accuracy are discussed, and other variables that may influence anticipatory saccades including the predictability of the pitch and the level of batter expertise are described. Further studies involving larger groups with different levels of expertise under game conditions are required to determine which gaze tracking strategies are most beneficial for baseball batting.